PENGARUH TATA KELOLA PERUSAHAAN, UKURAN PERUSAHAAN DAN UMUR PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Mikha Tri Apriliani; Totok Dewayanto (Diponegoro Journal of Accounting, 2018)
This study purpose to provide empirical evidence of corporate governance, firm size and firm age as influence mechanism to firm performance. This study use board size, board independence and board female diversity as mechanism of corporate goverance. Data used in this study was secondary, annual report and financial reporting from chemical and basic industry sectors, the various sectors of the industry and the consumer goods industry sectors listed on the Stock Exchange in 2013-2015. The population of this study was 420 companies from chemical and basic industry sectors, the various sectors of the industry and the consumer goods industry sectors listed on the Stock Exchange in 2013-2015 The sample of this study was 278 companies. The sample drawn by sample selection criteria. The analysis used to answer the study objectives is to use multiple regression. The result of the research show the effect of board size and firm age to firm performance, where board independence, board female diversity and firm size do not effect to firm performance. For the manager, firm performance information used in decision making to determinethe policy to be taken.